1‐Carboxymethyl‐3‐methyl‐1H‐imidazol‐3‐ium chloride 2‐(3‐methyl‐1H‐imidazol‐3‐ium‐1‐yl)acetate monohydrate: a crystal stabilized by imidazolium zwitterions. (5th September 2013) - Zhang, Heng; Chang, Liangliang; Wang, Na; Xuan, Xiaopeng
Abstract : The title compound, C6 H9 N2 O2 + ·Cl − ·C6 H8 N2 O2 ·H2 O, contains one 2‐(3‐methyl‐1 H ‐imidazol‐3‐ium‐1‐yl)acetate inner salt molecule, one 1‐carboxymethyl‐3‐methyl‐1 H ‐imidazol‐3‐ium cation, one chloride ion and one water molecule. In the extended structure, chloride anions and water molecules are linked via O—H...Cl hydrogen bonds, forming an infinite one‐dimensional chain. The chloride anions are also linked by two weak C—H...Cl interactions to neighbouring methylene groups and imidazole rings. Two imidazolium moieties form a homoconjugated cation through a strong and asymmetric O—H...O hydrogen bond of 2.472 (2) Å. The IR spectrum shows a continuous D‐type absorption in the region below 1300 cm −1 and is different to that of 1‐carboxymethyl‐3‐methylimidazolium chloride [Xuan, Wang & Xue (2012). Spectrochim. Acta Part A, 96, 436–443].